Effect Of Seed Hydration-Dehydration Integrated With Rhizobacteria On Viability And Vigor Of Deteriorated Soybean Seed - P.K. Dewi Hayati (JERAMI : Indonesian Journal of Crop Science, 2018)
Soybeans undergo rapid deterioration due to its chemical composition and unfavourable storage conditions. The objective of the research was to determine the length period of seed hidration and dehydration which is integrated with rhizobateri to viability and vigor of deteriorated soybean seed. A completely randomized design with four replicates were used in this experiment. Seeds were treated with varied combination of hydration period in a rhizobacteria suspension and followed by dehydration time. Data were analysed using the F-test and significant differences were further tested with Least Significant Difference at the 5% level. Results showed that the hydration and dehydration period of seeds in a rhizobacteria suspension improved viability and vigor of seed which have 59.5% initial germination percentage. The improvement was 12.28%, 0.56, 25.4% and 1.4 days for standard germination test, vigor index, first count test percentage and T50, respectively. The hydration for 60 minutes followed by dehydration for 60 minutes gave the best results on seed viability and vigor.